2018
DOI: 10.1063/1.5026422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ischaemic crisis using the informational causal entropy-complexity plane

Abstract: In the present work, an ischaemic process, mainly focused on the reperfusion stage, is studied using the informational causal entropy-complexity plane. Ischaemic wall behavior under this condition was analyzed through wall thickness and ventricular pressure variations, acquired during an obstructive flow maneuver performed on left coronary arteries of surgically instrumented animals. Basically, the induction of ischaemia depends on the temporary occlusion of left circumflex coronary artery (which supplies bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The complexity–entropy causality plane (CECP) was introduced by Rosso et al [ 43 ] as a tool to jointly quantify both information content and structural complexity in a temporal series. It was shown that CECP is useful for distinguishing between stochastic noise and deterministic chaotic behavior [ 43 ], leading to many applications in data analysis such as in physiology [ 44 ], physics [ 45 , 46 ], oceanography [ 47 ], ecology [ 48 ], hydrology [ 49 , 50 , 51 ], and finances [ 27 , 28 , 29 , 30 ]. In CECP representation, the horizontal axis is the Permutation entropy, and the vertical axis is a statistical complexity measure, also calculated using Bandt–Pompe probability distribution .…”
Section: Methodsmentioning
confidence: 99%
“…The complexity–entropy causality plane (CECP) was introduced by Rosso et al [ 43 ] as a tool to jointly quantify both information content and structural complexity in a temporal series. It was shown that CECP is useful for distinguishing between stochastic noise and deterministic chaotic behavior [ 43 ], leading to many applications in data analysis such as in physiology [ 44 ], physics [ 45 , 46 ], oceanography [ 47 ], ecology [ 48 ], hydrology [ 49 , 50 , 51 ], and finances [ 27 , 28 , 29 , 30 ]. In CECP representation, the horizontal axis is the Permutation entropy, and the vertical axis is a statistical complexity measure, also calculated using Bandt–Pompe probability distribution .…”
Section: Methodsmentioning
confidence: 99%
“…All efforts to understand the statistical properties of PE are important since this complexity measure was widely applied in Applied Science. Permutation Entropy was used in many different applied science for example Mechanics Engineering [9,10], Epilepsy [11][12][13], Anesthesia [14], Cardiology [15,6,16], Finance [17], Climate Change [18]. We refer to [19,20] for a comprehensive review of the Permutation Entropy application and its evolution through years.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Legnani et al (2018) analyzes the evolution of an ischaemic process using causal Information Theory descriptors. Ischaemic wall behavior under this condition was analyzed through wall thickness and ventricular pressure variations, acquired during an obstructive flow maneuver performed on left coronary arteries of surgically instrumented animals.…”
Section: Introductionmentioning
confidence: 99%